A critical analysis of the Language Background Other Than English (LBOTE) category in the Australian national testing system: a Foucauldian perspective. Issue 3 (3rd May 2016) - Creagh, Sue
Abstract: This article presents a Foucauldian analysis of the political rationalities of national testing and accountability practices in Australia, and their inconsistencies for students for whom English is a second or additional language. It focuses on a problem associated with the statistical data category 'Language Background Other Than English' (LBOTE) in the Australian national testing system. There is large variation in the performance of LBOTE students, but the average score of the group serves to homogenise the category and silence the association between language and test performance. Using Foucault's ideas about governmentality and disciplinary power, this article examines the technologies of power evident in the Australian education reforms, in order to challenge a particular version of reality, created by the LBOTE category. The impact of disciplinary power on English as a Second Language (ESL) teachers is signalled, as they navigate the dual demands of meeting education accountabilities whilst supporting high needs ESL learners. This article challenges the idea that current accountabilities are able to address the goal of equity for all Australian students, rather suggesting that a focus on test performance, represented by statistical categories like LBOTE, undermines implementation of specialist pedagogy, and demands that teachers transform their practice to satisfy systemic need rather than student need.